Peace : A Very Short Introduction - Richmond, Oliver P. (Oxford, New York Oxford University Press, 2014)
The modern concept of peace has broadened from the mere absence of violence to something much more sophisticated, incorporating terms such as 'peacemaking' and 'conflict resolution'. In this Very Short Introduction, Oliver Richmond explores the evolution of peace in practice and in theory, considering our modern assumptions about peace.
Include Index and Illustration
Keywords: Peace -- Peace-building -- Peace--International cooperation